Мотивація вибору абітурієнтами освітньої програми «Соціальне забезпечення»: свідомий крок чи випадковість? - Медіна, Тетяна Вячеславна; Шестакова, Катерина Юріївна (Харків: Вид-во НУА, 2021)
The motivation of the entrant's choice of educational program and free economic education provides an understanding of how the university can diversify the areas of career guidance work. In order to study the motivation for choosing the educational program “Social protect” in January 2021 among students 1-4 courses of specialty 232 “Social protect” conducted an online survey at the Chernivtsi National University named after Yuri Fedkovych. As a result of the research, it was found that the majority of entrants when entering this educational program are not oriented to employment opportunities in the specialty. The primary motives for choosing the specialty “Social protect” is the opportunity to enter the budget form of education. Other important factors include the prestige of the institution and the attractiveness of the city and region. The lack of student deductions, as well as the positive attitude of parents of entrants indicate that they are not disappointed in their own choice, so the university should make more efforts to promote this educational program.
Абітурієнтське середовище періоду глокалізації: шляхи формування та тенденції розвитку: Матеріали XIX Міжнар. наук.-практ. конф., Харків, 12 лют. 2021 р.
Keywords: Еntrant, social protect, motivation to choose an educational program